Three-Phase PWM Voltage-Source-Inverter Weight Optimization for Aircraft Application Using Deterministic Algorithm - Voldoire, Adrien; Schanen, Jean-Luc; Ferrieux, Jean-Paul; Derbey, Alexis; Gautier, Cyrille (Electronics (Basel), 2020)
In this paper, a design by optimization process is used to size a 10-kW three-phase pulse width modulation (PWM) inverter for aeronautic application. The objective function is the converter weight, which has to be minimized. Sizing constraints are the efficiency, alternating current (AC) and direct current (DC) harmonics, and thermal constraints on all devices. A deterministic algorithm is chosen since it allows obtaining quick results and dealing with a large number of variables. All equations are analytical, in order to comply with this gradient-based optimization strategy, which imposes the derivability of the models. Several optimization results using different AC inductor solutions (iron powder and ferrite) are compared. The optimized converters were built and tested experimentally to verify their performances. Semiconductor and inductor losses were measured accurately using calorimetric test benches. The optimality of the solutions was carefully verified by changing parameters.